Short-term effect of Tramadol injection on the serum levels of Follicle Stimulating Hormone, Luteinizing Hormone and Testosterone in Male Sahel Goats in Maiduguri, Nigeria - Bako, Babagana; Malami, Sani; Uthman Sadiq, Garba; Gana Ashiekh, Lawan (International Journal of Pharmacology and Toxicology, 2019)
Tramadol is a synthetic analogue of codeine. Its mood elevation property and sex enhancement potentials are the main reason for its abuse. The aim of the study was to determine the short-term effect of tramadol administration on Follicle Stimulating Hormone (FSH), Luteinizing Hormone (LH) and Testosterone (TEST) levels in Male Sahel Goats. This was an experimental study conducted from 1st October 2017 to 12th November 2017 at the Livestock Teaching and Research Farm, University of Maiduguri, Maiduguri, Borno State Nigeria involving 20 Male Sahel Goats. The goats were divided in to 4 groups of 5 each; group 1 served as control and groups 2, 3 and 4 were injected intramuscularly with 4 mg/kg (low dose), 8 mg/kg (medium dose) and 12 mg/kg (high dose) of Tramadol respectively. The injections were given intramuscularly, 3 times a week for 4 weeks. Blood samples were collected to determine the serum levels of FSH, LH and TEST at 0, 1 week, 2 weeks, 3 weeks and 4 weeks of tramadol injections. The MeanÂ±SD of the hormones were computed using SPSS 20. The difference in mean was compared using t test and ANOVA with p < 0.05 set for statistical significance. The baseline levels of FSH, LH and TEST in Male Sahel Goat in Maiduguri were 2.91Â±5.74 Miu/ml, 0.29Â±0.72 Miu/ml and 3.92Â±6.39 ng/ml respectively. Only the goats in group 4 showed a significant increase in serum FSH and LH by the 4th week (P=0.01 and 0.03 respectively) while no significant change was noted in the other groups. The was a decline in the level of Testosterone from 1st week through 4th week in all the experimental group but the level in the control group remain fairly constant throughout the experiment. The decline is inversely proportional to the dose of tramadol injection and most marked in group 4.High dose and prolonged used of Tramadol should be avoided because of side effects of Hypergonadotrophic hypogonadism.Â Â